Penilaian Keanekaragaman Hayati Hutan Kota Nyaru Menteng, Kelurahan Tumbang Tahai, Kecamatan Bukit Batu, Kota Palangka Raya, Provinsi Kalimantan Tengah: Biodiversity Assessment of Nyaru Menteng Urban Forest, Tumbang Tahai Village, Bukit Batu District, Palangka Raya City, Central Kalimantan Province - Yulianto, Santosa; Arianto, Rahmad Ade; Setiawan, Moch. Arifin; Yulianti, Reri (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
Nyaru Menteng Urban Forest is ±100 hectares of Others Use Area (APL) and information on its biodiversity is limited. This study aims to assess biodiversity and forest conditions. Flora data were collected using the quadrat transect method and fauna data using a combination of Visual Encounter Survey and Point Count methods. The species composition of the flora is no less than 20 species, dominated by the Dipterocarpaceae family with density of seedling 6,170 individuals/ha, saplings 1,472 individuals/ha, poles 330 individuals/ha, and trees 224 individuals/ha indicating sufficient natural regeneration and forming an inverted J curve. The highest IVIs were Combretocarpus rotundatus, Shorea balangeran, Cratoxylon glaucum, Campnosperma coriaceum, and Palaquium leiocarpum. Flora biodiversity shows high species diversity, high species richness, low species dominance, and almost even species distribution. Fauna species composition is 45 species with 6 species of mammals, 25 species of avifauna, 7 species of herpetofauna, and 7 species of insects. Faunal biodiversity showed moderate species diversity, low species dominance, low species richness (except avifauna), and moderate species evenness. It can be concluded that Nyaru Menteng Urban Forest is very worthy of being maintained as an exotic and unique peat swamp forest, because it has high biodiversity with abundant natural regeneration, good individual species evenness, stability and balance of the forest ecosystem